The new Negro : readings on race, representation, and African American culture, 1892-1938 - Gates, Henry Louis, Jr; Jarrett, Gene Andrew, 1975- (Book collections on Project MUSE., 2007)
When African American intellectuals announced the birth of the ""New Negro"" around the turn of the twentieth century, they were attempting through a bold act of renaming to change the way blacks were depicted and perceived in America. By challenging stereotypes of the Old Negro, and declaring that the New Negro was capable of high achievement, black writers tried to revolutionize how whites viewed blacks--and how blacks viewed themselves. Nothing less than a strategy to re-create the public face of ""the race, "" the New Negro became a dominant figure of racial uplift between Reconstruction an